بناء نموذج ریاضی لاختیار واسطة النقل للرحلات المنجذبة إلى مدنیة الرمادی - nan, nan; nan, nan; nan, nan; nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2008)
Ramadi city is one of the cities, which needs to a comprehensive transportation studies because of the change in the economic and social state of the population. This change cause an increasing in the number of population and the proportion of owns the vehicle, thus increasing the number of trips, thereby making them suffer jamming in the transportation network at peak hours. For purposes of this study, the city were divided into 18 zones in which data has been collected for special statement makers trips (the rate of income, vehicle ownership,...... etc.), the purpose of the trip, and the characteristics of transportation modes (the time of trip, the cost of the trip ,.... ... etc). A model was building for the purpose of the trip (shopping trip, working trip, and education trip) to predict the percent of contribution of each type of transportation modes for trips attraction to the city, by finding of the relationship between them and the characteristics of trip ,trip-makers and transportation modes. a strong linear equations where found after analysis by multi-linear regression and these equations can be used in the future forecasting for the city.